Zur regionalen Differenzierung von Wassernutzungsabgaben - Gawel, Erik; Möckel, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
Regulatory water use charges aim at restructuring water uses according to scarcity of regional water services. Hence, a spatial differentiation of the charge design appears to be an appropriate means of water pricing policy. Similarly, the European Water Framework Directive with its requirement of regional water resources management and its focus on river basins and water bodies could demand or indicate regional differentiations. However, in Germany two water use charges exist mainly unrelated to regional scarcity patterns: a nationwide effluent charge and different water extraction charges in 11 German States. Moreover, in 2006 the federal government has obtained the competence to implement a nationwide charge on water withdrawal without any regional differentiations. Against this background, the paper analyses the scope and limitations of regionally differentiated water use charges in Germany. First, the Water Framework Directive is examined as to whether the so-called combined approach of both emissions and immissions requirements makes a regional approach for charges mandatory. Second, the paper investigates the main conceptual elements and options of a regionalisation and their ecological, economic, legal and political aspects. The authors conclude that regionally differentiated water use charges are feasible as well as justifiable. However, with particular respect to the environmental objectives of protection of coastal water and marine ecosystems an effluent charge should still provide nationwide incentives according to the emissions principle. For water extraction charges the authors recommend a nationwide regulation framework yet completed by legal options for regional differentiations on e.g. water body level.
Keywords: Effluent charge; Water extraction charge; Water Framework Directive; Regional differentiation; Combined approach; Water body